The effect of participation in a mobility clinic on self-reported mobility and quality of life in people with lower limb amputation: A pilot study. (August 2020) - Anderson, Sarah; Ridgewell, Emily; Dillon, Michael
Background: Many people with lower limb amputation experience mobility impairment and reduced quality of life. Mobility clinics are designed to improve mobility and quality of life for people with lower limb amputation, but their effectiveness is unknown. Objectives: To compare changes in mobility prior to, and 12 weeks following participation in mobility clinic for people with lower limb amputation, and to explain whether changes in mobility explained changes in quality of life. To determine whether the PLUS-M™ was sensitive to the effects of participation in the mobility clinic, and to estimate the sample size required for a definitive study. Study design: Longitudinal observational. Methods: Electronic versions of the PLUS-M and SF-36v2 ® were completed by people living in the community with lower limb amputation prior to, and 12 weeks following participation in a mobility clinic. Results: There was a significant increase in mobility from baseline to 12 weeks post participation in the clinic ( p  = 0.012). Changes in mobility explained a significant proportion of variance in the SF-36v2 mental component summary ( p  = 0.024) but not the physical component summary ( p  = 0.804). Conclusion: For people with lower limb amputation, mobility increased after participation in the clinic and this explained improvements in SF-36v2 mental component summary. The PLUS-M was sensitive enough to detect a change in mobility over time. Clinical relevance: This preliminary data indicated that participation in a mobility clinic improved mobility and the mental components of quality of life for people living with lower limb amputation. The PLUS-M™ seems sensitive to changes in mobility as a result of participation in a mobility clinic.